Microfluidic Paper-Based Analytical Device (μPAD) for Determining Hydroquinone in Facial Whitening Cream using Phloroglucinol Reagent - Sulistyarti, Hermin; Puspitaloka, Paradhita Ayu; Putra, Boyfannie Ivan; Retnowati, Rurini; Tolle, Herman (Makara Journal of Science, 2021)
A microfluidic paper-based analytical device (µPAD) is developed in this work to analyze hydroquinone in facial whitening creams using phloroglucinol. The µPAD features a hydrophobic barrier for detection and was fabricated using a wax printer with Whatman chromatographic paper. Detection was achieved by colorimetry based on the formation of an orange hydroquinone–phloroglucinol complex. The colored reaction product formed on the detection zone of the µPAD was scanned, and the images obtained were processed with Image-J software to determine their color intensity (RGB value). Optimization of the process conditions was conducted to achieve sensitive measurements. The optimum conditions yielding maximum sensitivity included a reagent addition sequence of phloroglucinol à NaOH à sample (hydroquinone), 1 µL of 0.5% phloroglucinol, 1 M NaOH, and 10-minute reaction. Under optimal conditions, the µPAD produced two linear calibration curves for hydroquinone at concentrations of 10–100 mg/L (R2 = 0.9979) and 250–1000 mg/L (R2 = 0.9991). The method demonstrated very good selectivity for the target analyte in the presence of propylene glycol and resorcinol with satisfactory validity and average recovery close to 100%. The proposed µPAD is a very simple and inexpensive technique for hydroquinone analysis and could be applied to cosmetics samples with satisfactory results.